2014
DOI: 10.1186/1752-4458-8-44
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal stress during pregnancy and offspring internalizing and externalizing problems in childhood

Abstract: BackgroundMaternal psychological health during pregnancy has been associated with offspring psychopathology. However, it is uncertain whether these associations are mediated by the postpartum depression and related child-rearing factors. Therefore, we examined the associations between prenatal and postnatal factors and internalizing and externalizing behavioral problems in childhood, focusing on maternal psychological health in school-aged children in Korea.FindingsThe current study included 1,003 children (58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
(20 reference statements)
5
27
0
1
Order By: Relevance
“…In particular, accumulating research suggests that maternal stress during pregnancy is related to childhood cognitive difficulties frequently seen in the histories of depressed populations (Hofstra et al, 2002; Wood et al, 2013), such as lower scores on tests of intellectual functioning and language abilities (Laplante et al, 2008; Slykerman et al, 2005), problems of attention/concentration (Brouwers et al, 2001; Gutteling et al, 2006), and difficultites in academic performance (Niederhofer and Reiter, 2004). Additionally, prenatal maternal stress has been associated with increases in offspring behavioral/emotional problems during childhood that are linked to risk of later depression (Zahn-Waxler et al, 2000), such as childhood anixety (Davis and Sandman, 2012; Loomans et al, 2011), parental report of behavioral maladjustment (Gutteling et al, 2005; O'Connor et al, 2002), internalizing problems (Howland et al, 2016; Park et al, 2014), and temperaments associated with increased frustration, crying, and negative reactivity (Davis et al, 2007; Gutteling et al, 2005; Werner et al, 2007). Evidence also suggests sex differences in fetal exposure to prenatal stress with females showing an increased risk for later affective problems compared to males, following fetal exposure to maternal stress (Quarini et al, 2016; Sandman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, accumulating research suggests that maternal stress during pregnancy is related to childhood cognitive difficulties frequently seen in the histories of depressed populations (Hofstra et al, 2002; Wood et al, 2013), such as lower scores on tests of intellectual functioning and language abilities (Laplante et al, 2008; Slykerman et al, 2005), problems of attention/concentration (Brouwers et al, 2001; Gutteling et al, 2006), and difficultites in academic performance (Niederhofer and Reiter, 2004). Additionally, prenatal maternal stress has been associated with increases in offspring behavioral/emotional problems during childhood that are linked to risk of later depression (Zahn-Waxler et al, 2000), such as childhood anixety (Davis and Sandman, 2012; Loomans et al, 2011), parental report of behavioral maladjustment (Gutteling et al, 2005; O'Connor et al, 2002), internalizing problems (Howland et al, 2016; Park et al, 2014), and temperaments associated with increased frustration, crying, and negative reactivity (Davis et al, 2007; Gutteling et al, 2005; Werner et al, 2007). Evidence also suggests sex differences in fetal exposure to prenatal stress with females showing an increased risk for later affective problems compared to males, following fetal exposure to maternal stress (Quarini et al, 2016; Sandman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While we were underpowered to detect statistically significant associations between maternal experience of PTEs or SLEs during pregnancy and offspring GAD due to limited sample size, effect estimates observed in our study were in the expected direction. Indeed, several other studies that have identified a positive association between maternal trauma or stress during pregnancy and anxiety disorders in offspring during childhood (Najman et al, 2010;Davis and Sandman, 2012;Betts et al, 2014;Park et al, 2014). For example, Davis et al recently examined the association between maternal perceived stress during pregnancy and offspring anxiety at ages 6 and 9 assessed via the Anxiety Problems subscale of the Child Behavior Checklist (CBC) among a longitudinal cohort of 178 mother-child pairs recruited from obstetric clinics in Southern California (Davis and Sandman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While much research has focused on the role that early life trauma plays in the development of anxiety disorders among children (Stein et al, 1996;Pynoos et al, 1999;Heim and Nemeroff, 2001;Hovens et al, 2010Hovens et al, , 2012Hovens et al, , 2015Lochner et al, 2010;Klauke et al, 2011;Kuo et al, 2011;Zikic et al, 2015), a growing body of studies suggest that the adverse effects of traumatic events as well as other stressors on the development of anxiety disorders in children may begin before birth (Yehuda et al, 2001;Najman et al, 2010;Rice et al, 2010;Davis and Sandman, 2012;Betts et al, 2014;Park et al, 2014). Researchers have hypothesized that excess exposure to maternal stress hormones during gestation plays a key role in fetal programming of offspring anxiety disorders via causing permanent alterations to hypothalamic-pituitary-adrenal (HPA) axis function and/or via contributing to epigenetic modifications that adversely shape offspring stress reactivity (Weaver et al, 2004;Skinner et al, 2008;Glover et al, 2010;Davis et al, 2011;Radtke et al, 2011;Perroud et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, studies on the effects of parenting have focused on maternal aspects [15]. For example, many studies have suggested that antenatal and postnatal maternal depression negatively affects children’s cognitive and psychosocial development [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, many studies have suggested that antenatal and postnatal maternal depression negatively affects children’s cognitive and psychosocial development [14]. Maternal parenting stress directly influences infant development, has a negative effect on parenting behavior, and delays stable attachment between parent and child [6, 7].…”
Section: Introductionmentioning
confidence: 99%